Analisis Pembelajaran Pendidikan Agama Islam (PAI) dengan Pendekatan Pembelajaran Mendalam dalam Menumbuhkan Karakter Disiplin bagi Siswa Kelas 3 SD Negeri 1 Padokan Kabupaten Bantul - Ani Kusmawati; Mhd. Lailan Arqam; Sri Roviana; Azaki Khoirudin; Wantini Wantini (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Islamic Religious Education (PAI) instruction in elementary schools remains oriented toward knowledge transfer and rote memorization, resulting in the character trait of discipline not being optimally internalized. Meanwhile, the Independent Curriculum emphasizes meaningful and reflective learning through a deep learning approach. This study aims to analyze the design of deep learning-based PAI instruction, describe its implementation, and examine the strengthening of student discipline through this approach at SD Negeri 1 Padokan. The study employs a qualitative, descriptive approach. Research subjects included the school principal, the PAI teacher, and students. Data were collected through observation, in-depth interviews, and documentation. Data analysis utilized an interactive model comprising data reduction, data display, and conclusion drawing. Data validity was verified through source and technique triangulation. The results indicate that the instructional design was formulated within teaching modules that integrate principles of meaningful, mindful, and joyful learning. The implementation of instruction fostered active engagement, value reflection, and contextual practice, allowing the character of discipline to develop through habituation, role modeling, and positive reinforcement. Thus, deep learning proved effective in supporting the systematic and sustainable internalization of discipline, despite challenges regarding time constraints and administrative burdens.